ACOMPANHAMENTO DE EGRESSOS COMO FERRAMENTA PARA A GESTÃO UNIVERSITÁRIA: UM ESTUDO COM GRADUADOS DA UFBA - Lucas Carmo da Silva (Universidade Federal de Santa Catarina, 2017)
With the general objective of contributing to the understanding of the phenomenon of the transition to work, and specifically to provide indicators and elements for university mana gement, an investigation was conducted with 3648 students from the Federal University of Bahia (UFBA) from 64 courses in different areas, through online survey. Promoting the discussion about the impacts of university experience in the transition and conse quent graduate insertion in the labor market is the main evidence of the relevance and possibilities of improvement of student ́s experience. The results provide a rich source of elements for evaluating the effectiveness of institutional programs, especiall y in the context of extracurricular activities and the strengthening of entrepreneurship as a university management strategy. It is hoped that with systematic longitudinal monitoring data, a more accurate and specific analysis by courses will be possible, and that it will provide a basis for interventions focused on the quality of academic training.